Self-Instructional Material ‘Nai Dishayan’– A Training Module for Capacity Building of Teachers in Promoting Inclusive Education: An Evaluation - Dash, Manoj Kumar (INDIAN EDUCATIONAL REVIEW, 2013)
In India Capacity building of teachers and teacher educators at school level through distance mode started a decade back. The Distance Education Programme (DEP) a national component under DSE&L, MHRD, Govt. of India aims at effective utilisation/integration of technology for training of functionaries associated with school education across the country under Indira Gandhi National Open university. It supports in terms of design, development and implementation of Self Learning Materials (SLM) and other electronic materials also. DEPSSA in collaboration with SSA Uttarakhand developed a SLM ‘Nai Dishayan’ for training and orientation of functionaries associated with education of children with special needs at school level. The SLM was implemented across the state as a part of five days compulsory training of teachers in all seven blocks of Haridwar District. Therefore, a study was conducted to evaluate the effectiveness of this SLM in terms of capacity building of teachers, BRCCs/CRCCs and other SSA functionaries. The findings of the study would helps to review and update the SLM and develop strategic plan of action for its better implementation in future. This paper reflects many more strategies in the form of suggestions and implications for improving designing, development and effective implementations of SLM as training modules for recurrent training of teachers.